A Novel Virus-Like Agent Originated From Genome Rearrangement of Porcine Circovirus Type 2 (PCV2) Enhances PCV2 Replication and Regulates Intracellular Redox Status In Vitro - Feng, Huicheng; Fu, Jinping; Zhang, Bo; Xue, Tao; Liu, Chuanmin (Frontiers in Cellular and Infection Microbiology, 2022)
Genome rearrangement occurs to porcine circovirus type 2 (PCV2) during in vitro and in vivo infections, and a number of rearranged PCV2 genomes have been isolated and characterized. This study was conducted to investigate the role of the rearranged PCV2 (rPCV2) in PCV2 replication and the biological effect of rPCV2 in host cells. Two whole rPCV2 genome sequences (358 nt and 1125 nt in length) were synthesized and recombinant plasmids pBSK(+)-rPCV2 (pBSK(+)-1125 and pBSK(+)-358) were constructed. A novel virus-like agent (rPCV2-1125) was rescued by in vitro transfection of porcine kidney cell line (PK-15) and porcine alveolar macrophage 3D4/21 cells. The data indicate that rPCV2-1125 significantly enhanced PCV2 replication in vitro. Furthermore, rPCV2-1125 led to oxidative stress in host cells, as indicated by decreased intracellular glutathione (GSH) and total superoxide dismutase (SOD) activities, as well as increased malondialdehyde (MDA) levels. These results provide new insights into genome rearrangement of PCV2 and will contribute to future studies of PCV2 replication and associated mechanisms.